2020
DOI: 10.1098/rspb.2019.2442
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide exposure during brood or early-adult development reduces brain growth and impairs adult learning in bumblebees

Abstract: For social bees, an understudied step in evaluating pesticide risk is how contaminated food entering colonies affects residing offspring development and maturation. For instance, neurotoxic insecticide compounds in food could affect central nervous system development predisposing individuals to become poorer task performers later-in-life. Studying bumblebee colonies provisioned with neonicotinoid spiked nectar substitute, we measured brain volume and learning behaviour of 3 or 12-day old adults that had experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 82 publications
(126 reference statements)
1
54
1
1
Order By: Relevance
“…However, we found that polyfloral colonies, that had access to a lower amount of crude protein, reared both a lower number and mass of workersparticularly in the latter two weeks of our experiment (a similar pattern was observed for reared males). Producing a smaller and lighter workforce in polyfloral colonies may have implications for colony task performance, given that larger workers appear to show better learning and foraging performances (Goulson et al 2002;Spaethe and Weidenmüller 2002;Jandt et al 2009;Riveros and Gronenberg 2009;Willmer and Finlayson 2014;Smith et al 2020). The lack of any apparent compensatory strategy observed in our study is unlikely to be down to a reduced appetite, as the per capita consumption rate of both sucrose solution and pollen was not significantly different and actually higher on average in polyfloral colonies ( Figures S2-3).…”
Section: Individual Number:size Trade-offsmentioning
confidence: 70%
“…However, we found that polyfloral colonies, that had access to a lower amount of crude protein, reared both a lower number and mass of workersparticularly in the latter two weeks of our experiment (a similar pattern was observed for reared males). Producing a smaller and lighter workforce in polyfloral colonies may have implications for colony task performance, given that larger workers appear to show better learning and foraging performances (Goulson et al 2002;Spaethe and Weidenmüller 2002;Jandt et al 2009;Riveros and Gronenberg 2009;Willmer and Finlayson 2014;Smith et al 2020). The lack of any apparent compensatory strategy observed in our study is unlikely to be down to a reduced appetite, as the per capita consumption rate of both sucrose solution and pollen was not significantly different and actually higher on average in polyfloral colonies ( Figures S2-3).…”
Section: Individual Number:size Trade-offsmentioning
confidence: 70%
“…Therefore, neonicotinoids can act at multiple nAChR synapses in the mushroom body circuit, disrupting the plasticity-relevant signals for memory formation. Furthermore, in bees, field relevant concentrations of neonicotinoids disrupted mushroom body-mediated olfactory memory, electrically inactivated Kenyon cells 22 , decreased their synaptic density 26 and reduced antennal lobe Ca 2+ responses upstream of the mushroom body 27 . Additionally, neonicotinoids have been shown to interrupt mushroom body development 27 , providing a further route for memory disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in bees, field relevant concentrations of neonicotinoids disrupted mushroom body-mediated olfactory memory, electrically inactivated Kenyon cells 22 , decreased their synaptic density 26 and reduced antennal lobe Ca 2+ responses upstream of the mushroom body 27 . Additionally, neonicotinoids have been shown to interrupt mushroom body development 27 , providing a further route for memory disruption. Our results extend existing data from pollinators showing neonicotinoid disrupt memory by showing for the first time that the disruption is mediated by nAChRs containing Dα1 or Dβ2 subunits in the mushroom body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the stimulation of the mAChR of honeybee increases the volume of the mushroom body neuropil, which mimics the reinforcement of cholinergic neurotransmission in foraging bees 73 . A reduced mushroom body calycal growth is also associated with lower learning performance in bumblebees through micro-computed tomography scanning 74 . It would be interesting to investigate whether gut microbes impact the structural changes of the brain in future studies.…”
Section: Antibiotic Treatment Disturbs Social Behavior Via Regulatingmentioning
confidence: 99%